The role of visible wealth for deprivation - Veronika Bertram-Hümmer; Ghassan Baliki (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Motivated by the lack of literature linking actual to perceived relative deprivation, this paper assesses the role of visibility in the deprivation of goods and assets vis-à-vis income behind perceptions of relative deprivation. We rely on household survey data that includes unique information on reported perceived deprivation with a pre-specified reference group, namely others in the town or village. Based on a large number of asset and consumption items, we create an index of visible wealth by aggregating visible goods and assets using principal component weights. We find that relative deprivation in visible wealth has a ten percentage point higher explanatory power for reporting a high level of perceived deprivation than that of deprivation in income. The effect is robust under various sensitivity checks and for a number of controls. The finding sheds light on the importance of the visibility of the objects of comparison for an individual's assessment of his relative economic situation and proposes that future research should not solely rely on income-based deprivation measures.
Keywords: C23; C25; D31; I31; P3; 330; relative deprivation; visible wealth; income; comparison group